Saxa loquntur : Roman epitaphs from north-western Croatia = Rimski epitafi iz sjeverozapadne Hrvatske - Migotti, Branka, (Archaeopress Publishing Ltd, 2017)
This text examines Roman funerary material from three Roman cities of the south-western regions of the Roman province of Pannonia (modern-day north-western Croatia).